Theoretical and Numerical Analysis for Design of High Ratio Fiber Optic Taper Drawing Process - Jiahui Liu; Lili Zheng (IEEE Photonics Journal, 2020)
Fiber optic taper is an important component in the CCD coupling, television imaging and night vision device. Increasing need in high-resolution picture transmission devices requires better quality of high-ratio fiber optic taper. The resulting taper shape is important as it affects transmission properties of fiber optic taper. This paper develops a physical model for analyzing the high-ratio fiber optic taper time-dependent fabricating process. Based on the physical model, the evolution of the taper's neckdown profile is analyzed. Simulation results demonstrate that viscosity of materials, furnace geometry, temperature distribution in the furnace and the external tensile force will strongly affect the drawing process. The final shape of fiber optic taper depends on material properties and heating profile. The tensile force, which will affect the evolution process, has a minor influence on the taper's final shape. Based on the understanding of the above analysis, an improved drawing design can be proposed for fabricating large radius fiber optic taper with high ratio.